A Structural Critique and Analysis of The Sadegha-ye- Tabrizi’s Monshaat and the Study of the Insight and Method of the Scribe (11th century AH) - Reza Shah Maleki; Houshang Khosrow Beigi; Jamshid Noroozi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This research has made an effort to criticize the collection of Monshaat related to the 10th century AH written by Mirza Mohammad Sadegh Nazem Tabrizi (Sadegha-ye-Tabrizi) and to scrutinize the writer’s features, shortcomings, the importance of the manuscript, insight and method in a meaningful framework. The theme of the above version includes such concepts as royal decrees, court documents, an announcement of a victory, Monshaat and friendly correspondences from the Seljuk period to the early Safavid period that has not still been criticized and published and can in turn help to understand missing links in the political and social history of Iran and some of its neighbors. Relying on the manuscript of Tabrizi’s Monshaat and an analytical approach along with qualitative content analysis, this study indicates that the writer was influenced by the political atmosphere of the Safavid period in compiling and arranging the Monshaat. Since the Safavid’s ideal is explained to establish a national state on the basis of official religion and political boundaries, the writer has written documents that are linked to the geography which the Safavids sought to achieve in drawing their territorial model.